(25^4)^3:(4^2+3^2)^11-(0^2010+1^2012+2013^0)=
^=la puterea
Răspunsuri la întrebare
Răspuns de
6
Aplicam regulile de calcul cu puteri:
(25^4)^3:(4^2+3^2)^11-(0^2010+1^2012+2013^0)=
25^12:(16+9)^11-(0+1+1)=
25^12:25^11-2
25-2=
=23
(25^4)^3:(4^2+3^2)^11-(0^2010+1^2012+2013^0)=
25^12:(16+9)^11-(0+1+1)=
25^12:25^11-2
25-2=
=23
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă